AC Circuits - Davis, Chad (Open textbook library., 2017)
This eBook was written as the sequel to the eBook titled DC Circuits, which was written in 2016 by Chad Davis. This eBook covers Alternating Current (AC) circuit theory as well as a brief introduction of electronics. It is broken up into seven modules. Module 1 covers the basic theory of AC signals. Since only DC sources are used in the first eBook, details of AC signals such as sinusoidal waveforms (or sine waves), square waves, and triangle waves are provided. Module 2, titled AC Circuits Math Background, covers the mathematics background needed for solving AC circuit problems. The background material in Modules 1 and 2 are combined in Module 3 to solve circuits with AC sources that include resistors, inductors, and capacitors (RLC circuits).